Sex, Lies and TV: Censorship and Subtitling - Scandura, Gabriela (Meta, 2004)
AbstractThe following article deals with censorship and subtitled television programs. It is divided into three parts. The first part describes the reasons for censorship, including self-censorship. The second part explains the different types of censorship and gives examples of each, and the third part tries to explain the findings of a survey regarding audience awareness of subtitling censorship and reception of restrictions such as the use of a ‘Latin American’ Spanish.